FRI0320 MULTICENTER VALIDATION OF THE DETECTION OF ARTHRITIS IN INFLAMMATORY BOWEL DISEASES (DETAIL) QUESTIONNAIRE FOR THE SCREENING OF SPONDYLOARTHRITIS IN PATIENTS WITH INFLAMMATORY BOWEL DISEASES. (2nd June 2020) - Perini, L.; Benfaremo, D.; Marconi, V.; Paci, V.; DI Carlo, M.; Salaffi, F.; Luchetti, M. M.; Gabrielli, A.
Abstract : Background: Spondyloarthritis (SpA) is the most frequent extra-intestinal manifestation in inflammatory bowel diseases (IBD), since it may occur in up to 25% of patients. The early referral to a Rheumatology Unit may lead to proper treatment and better outcomes for patients with suspect SpA. Recently, we have developed and preliminarily validated a self-administered screening questionnaire, called DETection of Arthritis in Inflammatory boweL diseases (DETAIL) 1 . Objectives: To validate the DETAIL questionnaire in a multicenter cohort of IBD patients enrolled at ten Gastroenterology and Rheumatology Units in Italy. Methods: The DETAIL instrument is a 6-item questionnaire developed through a Delphi method 1 . From October 2018 to March 2019, consecutive adult patients with IBD, Crohn's disease (CD) or ulcerative colitis (UC), filled out independently the DETAIL in the outpatient waiting room. Thereafter, within 2 weeks a blinded rheumatologist assessed all the patients, irrespectively of the DETAIL results, and classified them to be affected or not by SpA according to ASAS criteria. The performance of the DETAIL was evaluated trough Bayesian analysis, defining for each item of the questionnaire the sensitivity, specificity, positive (LR+) and negative (LR-) likelihood ratios. Results: Overall, 418 IBD patients filled out the DETAIL questionnaire. Upon rheumatological evaluation, 102 (24.4%) patients received a diagnosis of SpA. Of the six questions, the best performances were found in item 6 (LR+ 3.77), reporting inflammatory back pain at night, and in item 3 (LR+ 3.31), exploring Achilles enthesitis. The presence of back pain lasting more than three months (LR+ 2.91), of back pain with inflammatory features (LR+ 2.55) and a history of dactylitis (LR+ 2.55), showed also a fairly good performance, whereas a history of peripheral synovitis was slightly worse (LR+ 2.16). The combination of at least three items answered affirmatively yielded a post-test probability of SpA of 75% or more. The presence of alternative diagnoses, such as osteoarthritis and fibromyalgia, represented a minor confounder. Conclusion: The DETAIL questionnaire is the first screening tool for the early detection of SpA/IBD that has been validated by a multicenter study group. References: [1]Di Carlo M, Luchetti MM, Benfaremo D, Di Donato E, Mosca P, Maltoni S, Benedetti A, Gabrielli A, Grassi W, Salaffi F. The DETection of Arthritis in Inflammatory boweL diseases (DETAIL) questionnaire: development and preliminary testing of a new tool to screen patients with inflammatory bowel disease for the presence of spondyloarthritis. Clin Rheumatol. 2018 Apr;37(4):1037-1044. Acknowledgments: We are grateful to all the members of the GRADES-IBD study group for their outstanding help in the enrollment of patients. We also would like to acknowledge the "Società Italiana di Gastro-Reumatologia" (SIGR) for its help and assistance in the constitution of the multidisciplinary network. Disclosure of Interests: None declared